Mana jemen Strategik Pemberdayaan Orang Tua /Wali Murid - Subiyanto, Subiyanto (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2011)
The relationship between the school community is essentially a very important tool in fostering and developing the growth of learners in school, the school as a larger social system for achieving educational goals effectively and efficiently. Empowering the community and the school environment is a key kebehasilan school learners. Schools are required to make co-operation between parents / guardians of students understanding between educational institutions, parents, and community to the success of education became a shared responsibility.Participation of parents / guardians of students are involved in a real / direct form of ideas, ideas, criticism, constructive support in the implementation of education for parents / guardians of students is a partner to deliver learners achieve my goals and personality formation, and establish communication intensive , proactive, professional, (parents / guardians of students called the school committee).